Clinical and Pathological Study of Avian Cholera in Layer Chickens in Babylon Province/ Iraq - Ubais, Suhad Ali; Al-Aqaby, Aamer Rassam Ali (American Journal of Biology and Natural Sciences, 2024)
Avian pasteurella infection may cause in different avian species and therefore, cause huge financial losses especially in layer production cycle where the infection considers as one of the important pathogens. However, specimens were taken from layer hens’ farm of Babylon province/ Iraq and transfer to laboratory to investigate pathological features of the infected chickens. Results of clinical signs consist of depression, loss of appetite, ruffled feathers, labored breathing. Characteristic gross pathological findings were localized infection of peritoneal cavity and oviduct. Also, there was petechial hemorrhage in uterus of layer hens. Petechial haemorrhage appears on abdominal fat of layers. As well as petechial hemorrhages and enlargement in liver of layer chickens revealed avian pasteurellosis in fowls. Conclusion consists of comprehensive information about clinical and gross postmortem lesion of layers of Babylon province. Moreover, the observed data may provide an overview on the significant threat of pathogen on layer chickens industry. Therefore, this investigation was important to develop effective strategies to control avian pasteurellosis.